2017
DOI: 10.1186/s12992-017-0273-1
|View full text |Cite
|
Sign up to set email alerts
|

“I cry every day and night, I have my son tied in chains”: physical restraint of people with schizophrenia in community settings in Ethiopia

Abstract: BackgroundA primary rationale for scaling up mental health services in low and middle-income countries is to address human rights violations, including physical restraint in community settings. The voices of those with intimate experiences of restraint, in particular people with mental illness and their families, are rarely heard. The aim of this study was to understand the experiences of, and reasons for, restraint of people with schizophrenia in community settings in rural Ethiopia in order to develop constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 45 publications
4
78
0
5
Order By: Relevance
“…The following are the factors related to pasung on people with mental illness. around their neighborhood and destroying the properties, the traditional or medical medication drop out (2,4,5,11,12). Violent behavior and properti destruction done by people with mental illness are the main factors on the act of pasung by family towards people with mental illness (2,11,12).…”
Section: Factors Related To Pasungmentioning
confidence: 99%
See 3 more Smart Citations
“…The following are the factors related to pasung on people with mental illness. around their neighborhood and destroying the properties, the traditional or medical medication drop out (2,4,5,11,12). Violent behavior and properti destruction done by people with mental illness are the main factors on the act of pasung by family towards people with mental illness (2,11,12).…”
Section: Factors Related To Pasungmentioning
confidence: 99%
“…around their neighborhood and destroying the properties, the traditional or medical medication drop out (2,4,5,11,12). Violent behavior and properti destruction done by people with mental illness are the main factors on the act of pasung by family towards people with mental illness (2,11,12). The violent behavior mainly triggered by medication drop out (2,11,13).…”
Section: Factors Related To Pasungmentioning
confidence: 99%
See 2 more Smart Citations
“…This hypothesis aligns with a qualitative study in Sodo District that found that the primary reason for restraint was to protect the individual with mental illness or to protect the community from the individual. This was particularly true when access to treatment was limited or nonexistent [51].…”
Section: Discussionmentioning
confidence: 99%